EFEKTIVITAS PENGELOLAAN DANA DESA DI DESA MUGIM DISTRIK METEMANI KABUPATEN SORONG SELATAN - SAREFE, METUSALA; PANGKEY, MASJE; LALOMA, ALDEN (JURNAL ADMINISTRASI PUBLIK, 2020)
The number of complaints from the community regarding the management of village funds by the villagehead and his officials starting from the planning stage of the implementation program, administration,reporting and accountability is not implemented transparently as well as the financial management ofvillage funds such as the provision of direct cash assistance (BLT) which is not distributed evenly to thecommunity. Weigh to choose even though it is according to government instructions. Based on theseproblems, this study aims to determine how the management of village funds in Mugin Village, MetemaniDistrict, South Sorong Regency This Research Is Designed As A Qualitative Research. This study aims todevelop or build a procession or explain the meaning behind reality. In qualitative research, research isbased on reality or events that take place in the field. The results showed that the management of villagefunds to improve facilities and infrastructure in Mugim Village, Metemani District was not optimal, thiswas because problems were still found in the planning, organizing, implementing and monitoring processes.Researchers will also reveal how the form of community interaction in managing village funds in order toimprove existing facilities and infrastructure in Mugim Village.Keywords: Effectiveness; Management; Village Fund